Experimental study of ligatures of the suprahepatic veins - Ramírez, Wilson; Sorondo, Martín; Tellechea, Miguel; Zinno, Alberto; Zubillaga, Daniel (Cirugía del Uruguay, 1978)
A study was conducted on the effect on the liver of ligature of suprahepatic vein. Survival proved possible depending on the territory affected by ligature. Furthermore, it also demostrated that histologic repercussion is related to evolution, since lesions become more obvious with time. Premature ascitis developed, although its causes are apt to disappear with time.